A gestão do Sistema Único de Assistência Social em Currais Novos (RN) - Oliveira, Ednara Gonçalves de (2009)
The present paper analyses the social assistance management in small cities, starting from the reality of Currais Novos City. Its main objective is to analyse the management of this politic in the context of the Nacional Sistem of Social Assistance (SUAS) through the management instruments materialized in the city: Social Assistance Plan, Budget, Management Report, Information Management, Monitorizing and Evaluation. It reveals a discrepancy between the instruments purpose and their concretude, and it identifies the main challenges in order to make them real, revealing the contradictions of such politic, through which the advances relate with the retrocesses. It remarks, in this context, the debate about Public Management and some aspects of the trajetory of the Social Assistance management in the brazilian context and the configurations of (SUAS) and of the politics in Currais Novos city. Such path allows us to identify the feebleness in the city ways to adopt the (SUAS) criteria, which is much more effective in burocratic aspects than in the change of the Social Assistance conception and in the effective incorporation of the (SUAS) principles and guidelines. Thus, problems are identified in what concerns to the important aspects for its effectivation, with the human resources, financing and social control mechanisms. It makes possible to reafirm the importance of the analysed management instruments for the effectivation of one participative and democratic management, as well as the urgency of its materialization as one of the important ellements for this politic to happen as a right and to make a stop to the unconformities between the (SUAS) determinations and its materialization